Options of improvement of efficacy of gastroesophageal reflux disease treatment by dioctaedric smectite - O. A. Storonova; A. S. Trukhmanov; N. Yu. Ivashkina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. To analyze efficacy of heartburn relief and pathological gastroesophageal reflux (GER) elimination as well as dynamics of endoscopic changes at gastroesophageal reflux disease (GERD) under dioctaedric smectite (Smecta) treatment in standard doze as monotherapy and within complex mode of treatment.Material and methods. Overall 45 case records of GERD patients (25 women and 20 men, mean age 43,06 years) were analyzed. All patients underwent esophagogastroduodenoscopy (EGDS) and 24-hour рН-impedance recording prior to the treatment onset and at the 14-th day of therapy. The first group included patients with erosive esophagitis (EE) of the I–II degree receiving combination of proton pump inhibitors (PPI) and Smecta, the second group included patients with EE, receiving PPI monotherapy, the third group — patients with non-erosive reflux disease (NERD) at Smecta monotherapy.Results. On a background of treatment by PPI + Smecta relief of heartburn was achieved at the 3rd day in 10 (66,7%) patients, at PPI monotherapy — in 4 (26,7%) patients with EE, at monotherapy by Smecta — in 6 (40%) patients. At the 5th day heartburn has been completely relieved in 11 (73,3%), 9 (60%) and 8 (53,3%), and at the 14-th day — in 13 (86,7%), 11 (73,3%) and 12 (80%) patients respectively. In the first group according to upper endoscopy data healing of erosions was confirmed in 13 (86,7%) patients, in the second — in 10 (66,7%). In the third group cessation of catarrhal signs was revealed in 13 (86,7%) patients. According to 24-hour рН-impedance esophageal recording prior at the beginning of therapy pathological acidic, weakly acidic and weakly alkalinic GERs were diagnosed in 34 (75,5%), 18 (40%) and 12 (26,7%) patients in group as a whole respectively. On a background of therapy by PPI + Smecta acidic refluxes have been eliminated in 14 (93%), at PPI monotherapy — in 11 (73%), at Smecta monotherapy — in 100% of patients. In the first group weakly acidic refluxes disappeared in 2 (67%), in the second — in 1 (50%), in the third – in 9 (69%) cases, weakly alkaline refluxes: in 4 (80%), in 2 (40%) and in 100% of cases respectively.Conclusions. Addition of Smecta in treatment mode at erosive form of GERD essentially increases treatment response rate, significantly reducing terms of clinical improvement onset. Dioctaedric smectite appears an effective drug as monotherapy of NERD. The chief advantage in treatment of GERD is ability of the drug to stop all reflux types: acidic, weakly acidic, and weakly alkalinic.